Internalizing the Values of Religious Moderation Through Rohis Extracurricular Activities to Prevent Radicalism - Eka Yuniarti; Evi hartiyanti; Annisa Gusti Ayu Pratiwi Gusti Ayu Pratiwi; Fitria Fitria; Fitri Yuliati Fitri Yuliati; M. Makhrus Ali; Tri Hariyati; Khairunesa Isa Isa (AFKARINA: Jurnal Pendidikan Agama Islam, 2025)
This study aims to analyze the process of internalizing the values of religious moderation through the Islamic Spirituality (Rohis) extracurricular activity as an effort to prevent radicalism at SMA N 1 Abung Barat. This study uses a qualitative approach with a case study type. Data were obtained through observation, interviews, and documentation involving the principal, Islamic Religious Education teachers, Rohis instructors, Rohis administrators, Rohis members, and students involved in school religious activities. Data analysis was carried out through the stages of data condensation, data presentation, and drawing conclusions, while data validity was maintained through source triangulation and technical triangulation. The results of the study indicate that Rohis plays a role as a space for educational and moderate religious development. Internalization of the values of religious moderation is carried out through three main patterns, namely habituation, exemplary behavior, and dialogue. The values instilled include tawassuth, tasamuh, i'tidal, anti-violence, religious literacy, digital literacy, social awareness, and national commitment. Rohis also serves as a preventative measure against radicalism by strengthening a peaceful understanding of religion, fostering a critical attitude toward religious information on social media, and fostering humanistic social experiences. Thus, Rohis can be a strategic instrument for schools in developing students who are religious, tolerant, critical, and nationally aware